Craniofacial and cutaneous findings in Noonan, Costello and LEOPARD syndromes - Pokrowiecki, Rafał; Chomik, Piotr; Borowiec, Maciej; Dowgierd, Krzysztof; Starzyńska, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Noonan, Costello and LEOPARD syndromes belong to a family of cardiofaciocutaneous disorders and share common genetic traits. As they are associated with a germline mutation in genes encoding proteins involved in RAS/MAPK, patients suffering from these syndromes are at a greater risk of cancer and abnormal myelopoiesis in infancy. Patients with cardio faciocutaneous syndromes share some clinically overlapping syndromes, therefore differential diagnosis can be problematic. In this paper we aim at demonstrating distinctive craniofacial and cutaneous manifestations of Noonan, Costello and LEOPARD syndromes which can be useful for clinicians who aim at treatment of children with rare diseases.